Evaluasi Kelayakan Teknis Dan FinansiaIndustri Pengolahan Hasil Perikanan LauDi Kabupaten Lampung Timurtl - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The evaluation of technical and financial feasibility of fishery processed industry in East Lampung Regency was investigated. The investigation used cluster random sampling method as sample taking technique. The financial feasibility criteria including Net Present Value (NPV), Net B/C Ratio, Internal Rate of Return (IRR), Pay Back Period (PBP), Break Event Point (BEP) and Sensitivity Analyze. The technical feasibilities are market aspect, raw material steady, facility and infrastructure steady. The result showed industries of fishery processing in East Lampung Region has potency to be developed. The highest level profit are powder fish processing (B/C 1,9), pindang soft bone fish (B/C 1,04 2,19), salt fish (B/C 1,07 1,19), fish crispy (B/C 1,06 1,16) and terasi (B/C 1,04 1,06). Keywords: technical and financial feasibility, fishery processed industry, evaluation.